2014 IEEE International Ultrasonics Symposium 2014
DOI: 10.1109/ultsym.2014.0124
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid extraction using a rapid, chemical free, ultrasonic technique for point-of-care diagnostics

Abstract: We have developed a miniature ultrasonic lysing system for the rapid release and extraction of Mycobacterium Tuberculosis (MTB) DNA. The prototype consists of two key sections, a disposable plastic manifold that hold sputum slides and a plastic cartridge with five fluidic DNA extraction channels. The MTB vaccine Bacillus Calmette-Guérin (BCG) was used as a simulant for MTB for all the lysing studies. The slide manifold houses up to five individual sputum slides and is processed by a computer to fill and load t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The details of the transducer operation and performance were cited previously [ 33 ]. Briefly, 36° Y-cut lithium niobate (90°, 90°, 36°) ( z, x, z ) excites a quasi-longitudinal wave with an electromechanical coupling of k t = 0.46 with an unloaded acoustic velocity of 7340 m/s.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The details of the transducer operation and performance were cited previously [ 33 ]. Briefly, 36° Y-cut lithium niobate (90°, 90°, 36°) ( z, x, z ) excites a quasi-longitudinal wave with an electromechanical coupling of k t = 0.46 with an unloaded acoustic velocity of 7340 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…The additional path length provided an additional tuning parameter between lysing efficacy and the subsequent nucleic acid extraction. For both interface types, Figure 4 b showed that increasing the applied power improved lysing efficiency, which required a balance between input power and heat generation by the transducer according to a thermal analysis [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations